2022
DOI: 10.1101/2021.12.29.21268505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Head-to-head comparison of nasal and nasopharyngeal sampling using SARS-CoV-2 rapid antigen testing in Lesotho

Abstract: Objectives To assess the real-world diagnostic performance of nasal and nasopharyngeal swabs for SD Biosensor STANDARD Q COVID-19 Antigen Rapid Diagnostic Test (Ag-RDT). Methods Individuals ≥5 years with COVID-19 compatible symptoms or history of exposure to SARS-CoV-2 presenting at hospitals in Lesotho received two nasopharyngeal and one nasal swab. Ag-RDT from nasal and nasopharyngeal swabs were performed as point-of-care on site, the second nasopharyngeal swab used for polymerase chain reaction (PCR) as the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Results presented here demonstrate that AN swabs are equivalent to NP swabs for SARS-CoV-2 Ag-RDT testing giving comparable sensitivities, 50% LoD and 95% LoD for both Ag-RDTs brands evaluated here. Our results supports previous findings where AN and NP swabs were compared for the Ag-RDT Standard-Q (SD Biosensor, Inc., Korea) in Lesotho [6], but we reported a higher sensitivity compared to the 67.3% and 70.2% for AN and NP swabs previously described [6]. Studies on RT-qPCR have found lower sensitivity using AN swabs compared to NP swabs consistently [5].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results presented here demonstrate that AN swabs are equivalent to NP swabs for SARS-CoV-2 Ag-RDT testing giving comparable sensitivities, 50% LoD and 95% LoD for both Ag-RDTs brands evaluated here. Our results supports previous findings where AN and NP swabs were compared for the Ag-RDT Standard-Q (SD Biosensor, Inc., Korea) in Lesotho [6], but we reported a higher sensitivity compared to the 67.3% and 70.2% for AN and NP swabs previously described [6]. Studies on RT-qPCR have found lower sensitivity using AN swabs compared to NP swabs consistently [5].…”
Section: Discussionsupporting
confidence: 91%
“…The order of sample collection could have negatively biased the results obtained for AN swabs caused by a possible sample depletion. However, in the two studies that compared Ag-RDT using AN swabs, the AN swab was collected first and our reported sensitivity and specificity for AN swabs are greater than the previous studies [6,7]. Further, studies on RT-qPCR found lower sensitivity using AN swabs compared to NP swabs [5], even when AN swabs were collected first [15,18,19].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the case of COVID-19 cases, a PCR test was used as the gold standard for diagnosis during most part of 2021. Later on, diagnosis was based on the result of the SARS-CoV-2 STANDARD Q COVID-19 Ag test, that has shown relatively low diagnostic performance in our setting (42). Anecdotically, a number of the 2252 (34%) eligible adults and children that presented with symptoms but did not enroll in this service model despite being eligible, were still tested for COVID-19 by the study staff, especially in periods were hospital health staff in other departments was scarce, however, these individuals are not included in this analysis.…”
Section: Comparison Performance Of Tb and Hiv Services With Similar H...mentioning
confidence: 99%
“…On the other hand, the overall TB and HIV linkage to care rates within four weeks of diagnosis were higher than reported in similar experiences (45)(46)(47)(48), however when comparing to global targets, this model fell short in ART initiation rates (75% vs 95%), and met the TB treatment initiation target (90% vs. 90%) (49,50). As the COVID-19 pandemic surged, and lockdowns led to the cancellation of essential health services, global health actors advocated to adapt services that integrated TB, HIV and COVID-19 activities in sub-Saharan Africa (29,(42)(43)(44). This established an emerging body of evidence that evaluates the experiences and successes in the integration of services.…”
Section: Comparison Performance Of Tb and Hiv Services With Similar H...mentioning
confidence: 99%